Use of BAER to identify loss of auditory function in older horses - Wilson, W. J.; Mills, P. C.; Dzulkarnain, Ahmad Aidil Arafat (John Wiley & Sons, Inc., 2011)
Objective: To use the brainstem auditory evoked response (BAER) to test the hypothesis that auditory function could be worse in older horses than in younger horses.